2022
DOI: 10.3390/antiox11040680
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with the Symbiotic Formulation Prodefen® Increases Neuronal Nitric Oxide Synthase and Decreases Oxidative Stress in Superior Mesenteric Artery from Spontaneously Hypertensive Rats

Abstract: In recent years, gut dysbiosis has been related to some peripheral vascular alterations linked to hypertension. In this work, we explore whether gut dysbiosis is related to vascular innervation dysfunction and altered nitric oxide (NO) production in the superior mesenteric artery, one of the main vascular beds involved in peripheral vascular resistance. For this purpose, we used spontaneously hypertensive rats, either treated or not with the commercial synbiotic formulation Prodefen® (108 colony forming units/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…In the present study, we aimed to evaluate the role of NO alterations in fetal programming of hypertension induced by maternal undernutrition during gestation, which we have previously demonstrated in adult male offspring [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we aimed to evaluate the role of NO alterations in fetal programming of hypertension induced by maternal undernutrition during gestation, which we have previously demonstrated in adult male offspring [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34],…”
Section: Discussionmentioning
confidence: 99%
“…This effect was sex-dependent and may be related to a higher superoxide anion production and/or to a lower elimination by antioxidant enzyme systems, since we have evidence that male rats of MUN model are deficient in antioxidants [ 33 , 34 ]. The smaller antioxidant capacity of MUN males was also evidenced by the low Nrf2, a factor that regulates adaptive response to oxidative stress promoting the transcription of antioxidant enzymes [ 4 ], and is downregulated in hypertensive animals [ 26 ]. The excess superoxide anion may be due to increased NADPH oxidase in the arterial wall, as we have demonstrated in mesenteric arteries from MUN males [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipidemia and obesity are commonly associated with oxidative stress, which is capable of modifying vascular tone by impeding NO bioavailability and signaling ( Čolak and Pap, 2021 ). During the oxidative stress state, excessive production of ROS reduces the bioactivity of NO due to its rapid oxidative inactivation by the ROS superoxide anion ( Mendez-Albinana et al, 2022 ). In alignment, it was observed in the current work that CAFD supplementation induced a significant reduction of NO circulating levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in hypertensive humans and animal models of hypertension have reported that supplementation with different prebiotic, probiotic, or synbiotic agents enhances acetate, butyrate, and propionate production, leading to the amelioration of hypertension [ 72 , 73 ]. In addition, increases in acetic, butyric, and propionic acids in plasma have been demonstrated after ingestion of FOS in different animal models, including SHR [ 74 , 75 ]. At the same time, long-term administration of L .…”
Section: Discussionmentioning
confidence: 99%